Mahasiswa IFTK Ledalero dan Isu HAM: Antara Teori Spiritualitas dan Aksi Nyata (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the role of students of IFTK Ledalero in responding to human rights (HR) issues through the integration of theoretical understanding, spirituality, and concrete action. The background of this research is rooted in the increasing complexity of human rights violations in Indonesia, particularly in marginalized communities, which demands a contextual and transformative response from academic institutions. The objective of this study is to analyze how students internalize human rights values from philosophical and theological perspectives and translate them into practical engagement. This research employs a qualitative descriptive method, using literature review and contextual analysis of student involvement in social issues. The findings indicate that while students possess strong theoretical foundations and spiritual motivations, there remains a gap in translating these into consistent and structured advocacy actions. However, emerging initiatives such as community service, pastoral engagement, and social campaigns demonstrate a growing awareness and commitment. The implication of this study emphasizes the need for a more integrative educational approach that bridges theory, spirituality, and praxis, enabling students to become transformative agents in promoting human dignity and justice.